The Pox party - Anderson, M. T. (Somerville, Mass. : Candlewick Press, 2011)
Various diaries, letters, and other manuscripts chronicle the experiences of Octavian, a young African American, from birth to age sixteen, as he is brought up as part of a science experiment in the years leading up to and during the Revolutionary War.
Booklist starred.
School Library Journal starred.
Wilson's Senior High School.
Booklist starred, September 2006.
Bulletin of the Center for Children's Books starre, November 2006.
Horn Book Starred, April 2007.
Keywords: African Americans -- Juvenile fiction; Liberty -- Juvenile fiction; Science -- Experiments -- Juvenile fiction; Slavery -- Juvenile fiction; African Americans -- Fiction; Freedom -- Fiction; Historical fiction; Science -- Experiments -- Fiction; Slavery -- Fiction; African Americans -- Fiction; Freedom -- Fiction; Historical fiction; Science -- Experiments -- Fiction; Slavery -- Fiction; Massachusetts -- History -- Revolution, 1775-1783 -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; Massachusetts -- History -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction; Massachusetts -- History -- Fiction; United States -- History -- 1775-1783, Revolution -- Fiction; Historical fiction